Geochemistry of Mn-bearing rocks hosted in rhyolites from Hadjer Bigli (SE Lake Chad, Cameroon Line): preliminary results - Mbowou,G.I.B.; Botelho,N.F; Ngounouno,I. (Journal of Geosciences, 2015)
Manganese-bearing rocks consisting of anhedral Mn- and Fe-oxyhydroxides (cryptomelane, goethite), kaolinite, tiny cerianite and zircon grains (< 10 m), and euhedral to subeuhedral quartz crystals, are hosted within rhyolitic rocks of Hadjer Bigli volcano (SE Lake Chad). Their Ce (1328 ppm) and Zn (1563 ppm) contents are increased, with high ΣREE values (1573 ppm).The Mn-rich rocks have been shown to be one of the most important environments for adsorption of some trace elements. The high Zn contents are considered to be the result of water-rock chemical reactions at intermediate to high temperatures. The sedimentary processes led likely to the concentration of manganese in the Lake Chad water and beneath, well before the volcanic activity. According to mineral chemistry and the whole-rock data, rhyolitic magma interacted with the near-surface manganese formations already concentrated by sedimentary processes.
Keywords: manganese; trace elements; Hadjer Bigli; Lake Chad; Cameroon Line